Potential risk to aquatic biota from aerial application of firefighting water additives. (1st January 2023) - Anderson, J.; Prosser, R.S.
Abstract: The frequency and severity of forest fires is increasing due to climate change. Consequently, there will be an increased use of forest firefighting additives, which increase the ability of water to extinguish fires and prevent reignition. Increased use will potentially result in increased exposure to aquatic ecosystems within forests. This study examined the toxicity of nine firefighting water additives that are currently on the market to three species of freshwater invertebrates that occupy different niches within freshwater ecosystems. The toxicity of the water additives varied up to three orders of magnitude. Pelagic and epibenthic invertebrates are affected at lower rates of application than endobenthic invertebrates. A field relevant application rate of three of the nine water additives tested represent a hazard to freshwater ecosystems under varies exposure scenarios represented by the depth of a theoretical water body (15–200 cm). This study highlights the importance of application buffers around water bodies and the selection of water additives that pose the lowest hazard to freshwater ecosystem, assuming that the efficacy of the additives in extinguishing fires is similar. Graphical abstract: Image 1 Highlights: Investigated toxicity of 9 firefighting water additives to 3 freshwater species. Toxicity varied by three orders of magnitude. Endobenthic invertebrates less sensitive then epibenthic or pelagic invertebrates. Three water additives posed a hazard under all scenarios.